Inventory of Ferns (Pteridophyta) at Cerme Cave Bantul District - Zuchrotus Salamah; Hadi Sasongko; Aulida Zulaikha Hidayati (UNIVERSITAS NEGERI PADANG, 2020)
Cerme Cave situated at Srunggo, Selopamioro village, Imogiri, Bantul District. Bantul has a supporting environment condition for ferns to grow and thrived. This research is conducted to produce an inventory of ferns grow within the Cerme Cave area. This research used explorative-method which include exploration, inventory, and fern identification activities. Descriptive analysis is used for data analysis. Result of this research showing that there are 17 species found within the Cerme Cave area, which are Drynaria quercifolia (Linnaeus) J. Smith, Pyrrosia longifolia (Burm. f.) C.V. Morton, Athyrium sp., Adiantum induratum Chirt, J. Bot. (Morot), Adiantum capillus-veneris Linn., Selaginella sp., Selaginella indica (Milde) R. M. Tryon, Adiantum philippense Linn., Pyrrosia petiolosa (Christ) Ching, Nephrolepis cordifolia (Linnaeus) C. Presl, Pteris vittata Linn., Pneumatopteris sp., Adiantum malesianum J. Ghatak, Hymenasplenium sp., Pneumatopteris sp., Pyrrosia nummularifolia (Sw.) Ching, Pteris sp.. Kata kunci: Cerme Cave, Pteridophyta